SEATING ARRANGEMENT IN IMPROVING STUDENTS' SPEAKING SKILL AT IQRA BURU UNIVERSITY - Riki Bugis (Al-Lisan: Jurnal Bahasa, 2018)
Speaking is one of the problems which is faced by anyone who learn English. In this research, the implementation of classroom management in this case seating arrangement aimed to find out to what extent seating arrangement improve students’ speaking skills at the second semester students of English Department of Letters Faculty at Iqra Buru University. The participants of this research were the English speaking lecturer and 30 students of Iqra Buru University. This research employed quasi experimental design, which consist of two groups namely control group and experimental group. Control group were treated by implementing orderly rows seating arrangement while for experimental were treated by implementing circle seating arrangement. The data were collected by using two kinds of research instruments namely test and recorder. The data were analyzed by statistical analysis SPSS program, version 20.0.The result shows that the implementation of seating arrangement can improve students’ speaking skill in term of accuracy, fluency and comprehensibility. It is supported by the mean score of the students’ posttests (74.48) was higher than pretests (56.07). on the other hand, there is also significant correlation among accuracy, fluency and comprehensibility.